2019
DOI: 10.1111/bcpt.13275
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinone ameliorates renal ischaemia–reperfusion injury by inhibiting apoptosis and inflammatory response

Abstract: Cryptotanshinone (CTS) is a natural compound from the Chinese herb Salvia miltiorrhiza. Previous studies demonstrated that CTS possesses anti-apoptotic and antiinflammatory properties. However, its effects and underlying mechanism on renal ischaemia reperfusion (IR) injury remain unknown. In the present study, we investigated the effects of CTS on renal IR injury and its potential underlying mechanisms.Mice were randomized into four groups as follows: (a) sham operation + vehicle, (b) sham operation + CTS, (c)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Among them, plant derived‐natural compounds are suggested to be beneficial in cancer therapy. A variety of factors contribute to the popularity of naturally occurring compounds in cancer therapy such as multi‐targeting, minimal side effects and low cost (Bai et al, 2019; Banik et al, 2020). These anti‐tumor drugs are abundant in nature and using them in cancer therapy can shed some light on their therapeutic effect to direct further studies in improving their anti‐tumor activity (Kashyap et al, 2019; Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, plant derived‐natural compounds are suggested to be beneficial in cancer therapy. A variety of factors contribute to the popularity of naturally occurring compounds in cancer therapy such as multi‐targeting, minimal side effects and low cost (Bai et al, 2019; Banik et al, 2020). These anti‐tumor drugs are abundant in nature and using them in cancer therapy can shed some light on their therapeutic effect to direct further studies in improving their anti‐tumor activity (Kashyap et al, 2019; Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cryptotanshinone (CPT), an active compound isolated from Radix Salviae Miltiorrhizae , has been reported to possess diverse pharmacological activities, including anti-fibrosis, neuroprotective, anti-inflammatory, anti-atherosclerotic, and antioxidant activities ( Mei et al, 2009 ; Wong et al, 2010 ; Ran et al, 2016 ; Lo et al, 2017 ; Bai et al, 2019 ; Sun et al, 2019 ; Zhou et al, 2019 ). For example, CPT reduced inflammation and oxidative stress in renal interstitial fibrosis by modulating the Nrf-2/HO-1 and NF-kappaB signaling pathways ( Wang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, these secreted inflammatory mediators would in turn further induce the accumulation of immunocyte and exacerbate inflammatory cascade (Rabb et al 2016 ). Increasing evidence has demonstrated that inhibition of inflammatory response may influence the development of ischemic AKI (Bai et al 2019 ). In recent studies, mindin ablation was demonstrated to inhibit IR mediated inflammatory responses in livers and brains and ameliorate organs damage (Sun et al 2015 ; Wang et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%